Dinamika Perbandingan Sosial dan Kepuasan Hidup pada Generasi Z: Peran Moderasi Harga Diri - Fadilla, Indri Resti; Ayriza, Yulia (Universitas Airlangga, 2025)
This study aimed to examine the effect of social comparison on life satisfaction with self-esteem as a moderating variable among Generation Z in Banten Province. A total of 391 participants aged 18–28 years participated in a quantitative survey with a cross-sectional design. Instruments included SWLS, INCOM, and RSES. Data were analyzed using Moderated Regression Analysis (PROCESS Model 1). Results showed that social comparison had a significant negative effect on life satisfaction, while self-esteem had a significant positive effect. However, the interaction effect between social comparison and self-esteem was not significant (p = 0.869), indicating that self-esteem did not moderate their relationship. These findings suggest that life satisfaction among Gen Z is more strongly influenced by self-esteem directly rather than through its interaction with social comparison.